High prevalence of mumps in Lao People's Democratic Republic. (6th March 2014) - Hübschen, J. M.; Vilivong, K.; Souvannaso, C.; Black, A. P.; Lütteke, N.; Samountry, B.; Phongsavath, V.; Khamphaphongphane, B.; Denny, J.; Sayyavong, C.; Woo, G. K. S.; Sengsaya, K.; et al.
Abstract In the Lao People's Democratic Republic (PDR), mumps is not a notifiable disease and mumps vaccine is currently not included in the routine childhood immunization programme. In order to assess the burden of disease, we investigated the seroprevalence of mumps‐specific IgG antibodies across four provinces. In addition, we genetically characterized mumps viruses from the past 3 years from several outbreaks and single cases. Blood and/or throat swabs from suspected cases were investigated for specific IgM antibodies or viral RNA. Mumps cases occurred between March and November in 2011–2013 and 5‐ to 15‐year‐olds were most affected. Four sequences from an outbreak in the north of Lao PDR in 2011 were identical and belonged to genotype G. Eight sequences from two outbreaks and two individual cases from 2012 and 2013 belonged to genotype J. In addition, sera collected from 2379 healthy infants and school pupils aged between 9 months and 19 years and from pregnant women aged between 16 and 46 years were investigated for mumps‐specific IgG. Overall, 58.2% were positive, 39.5% were negative and the remaining 2.3% were equivocal. The seropositivity increased with age, with the lowest percentage found in <1‐year‐old infants (9.1%) and the highest in the cohort of pregnant women (69.2%). More female subjects than male subjects were seropositive (60.4 vs. 54.9%). There were some differences between the locations. Mumps should be a notifiable disease in Lao PDR in order to get more accurate case numbers and cost estimates for public health‐care, and vaccination of children and high‐risk groups should be considered.